1991
DOI: 10.1103/physrevc.44.73
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization scheme for effective interactions

Abstract: An algorithm is developed by which two nucleon efFective interactions are constructed to fit onand off-shell t and-/or g-matrix elements. The effective interaction is defined as plane-wave matrix elements of local operators that may have explicit energy and medium dependences. It comprises central, tensor, spin-orbit, quadratic spin-orbit, and angular momentum square operators, all with Yukawa form factors. As examples, the Paris and Bonn potentials are used to construct t matrices for projection onto chosen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…These properties are quite inconvenient in various applications. In order to circumvent the problem, the Melbourne group showed that elastic scattering are determined by the on-shell and near-on-shell components of g matrix [21], and provided a local version of g matrix in which the potential parameters are so determined as to reproduce the relevant components [21,34,35]. The Melbourne g matrix thus obtained well accounts for NN scattering in free space that corresponds to the limit of ρ = 0, and the Melbourne g-matrix folding model reproduces NA scattering, as already mentioned in Sec.…”
Section: Local Version Of Chiral G Matrixmentioning
confidence: 99%
“…These properties are quite inconvenient in various applications. In order to circumvent the problem, the Melbourne group showed that elastic scattering are determined by the on-shell and near-on-shell components of g matrix [21], and provided a local version of g matrix in which the potential parameters are so determined as to reproduce the relevant components [21,34,35]. The Melbourne g matrix thus obtained well accounts for NN scattering in free space that corresponds to the limit of ρ = 0, and the Melbourne g-matrix folding model reproduces NA scattering, as already mentioned in Sec.…”
Section: Local Version Of Chiral G Matrixmentioning
confidence: 99%
“…The Melbourne group showed that elastic scattering are mainly determined by the on-shell part of g(ρ) [16]. Making a χ 2 fitting to the onshell and near-on-shell components of the g matrix, the group provided g(ρ) with a local (Yukawa) form in order to make the folding procedure feasible [16,32,33]. The Melbourne g matrix thus obtained accounts for NN scattering in the limit of ρ = 0, and the SF model based on the Melbourne g matrix explains NA scattering systematically with no adjustable parameter, as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we consider heavier targets such as 40 Ca, 58 Ni and 208 Pb to make our discussion clear, since the g matrix is evaluated in nuclear matter and the g-matrix folding model is considered to be more reliable for heavier targets. Taking the Melbourne-group procedure [16,32,33], we provide the chiral g matrix with a 3-range Gaussian form for each of the central, spin-orbit and tensor components, since the Gaussian form is much more convenient than the Yukawa form in many applications whereas the two forms yield the same results for NA and AA scattering. The ranges and the depths of individual components are determined for each energy and density so as to reproduce the on-shell and near-on-shell matrix elements of the original g matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Toyokawa et al localized the non-local chiral g matrix into three-range Gaussian forms by using the localization method proposed by the Melbourne group [2,13,14]. The resulting local g matrix is called "Kyushu g-matrix"; see the hompage http://www.nt.phys.kyushu-u.ac.jp/english/gmatrix.html for Kyushu g-matrix.…”
mentioning
confidence: 99%